Preparedness and response plan at Lumbini Medical College and Teaching Hospital, Palpa for COVID-19 pandemic - Bom, Rabin (Journal of General Practice and Emergency Medicine of Nepal, 2020)
Respiratory illness caused by novel corona virus became global pandemic. The disease is named COVID-19, meaning coronavirus disease 2019. Most of the districts of Nepal became infected with COVID-19. This COVID-19 became challenging aspect for both health personals and government. With emerging data and guidelines on COVID-19 most of health institutions in Nepal started to fight against it. We medical staffs at Lumbini Medical College and Teaching Hospital (LMCTH) realized need of early preparedness and response plan to tackle the rapidly emerging COVID-19 situation over nation.